Unilateral Complete Ptosis after Scalp Block for Awake Craniotomy: A Rare Complication - Hassan, Mohamad Hasyizan; Hassan, Wan Mohd Nazaruddin Wan; Kandasamy, Regunath; Chong, Soon Eu (Journal of Neuroanaesthesiology and Critical Care, 2018)
A combination of scalp block and monitored anesthesia care (MAC) is one of the options among anesthetic techniques that can be used during an awake craniotomy for epilepsy surgery. Even though a scalp block is useful as locoregional analgesia during the surgery, it also has the potential to cause some complications. Trigeminocardiac reflex and transient facial nerve palsies have previously been reported following scalp block. The toxicity of local anesthetic agents and nerve injuries present other potential complications. However, complete unilateral ptosis is a rare complication after scalp block. We report a case of unilateral complete mechanical ptosis after a scalp block using ropivacaine 0.75% for an awake craniotomy for epilepsy surgery.
Keywords: awake craniotomy; scalp block; ptosis; ropivacaine